2022
DOI: 10.1115/1.4056245
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of the Effect of Heat Sinks With Various Fin Geometries on the Performance of a Thermoelectric Generator

Abstract: In this study, effect of heat sink geometries on the performance of a thermoelectric generator was researched. In this context, fins with different geometries (flat fin, square pin fin, hexagonal pin fin, circle pin fin) placed to aluminium heat sink and their effects on heat transfer and electricity generation were investigated numerically. Calculations were carried out according to three different hot surface temperatures and five different air velocities. As a result of this study, it was determined that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Singh et al [20] explored the heat transfer characteristics of embossed heat sinks subjected to natural convection and found that the Nusselt number for embossed fin increased with the impression angle and pitch. The effect of heat sink geometries on the performance of a thermoelectric generator was researched by Özbektas et al [21], who found that the electrical output increased with increasing air velocity and surface temperature. The application of heat sinks with a similar structure in a heat exchanger devices has not been thoroughly investigated, nor have the pressurized directional flow characteristics or the impact of the geometric parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al [20] explored the heat transfer characteristics of embossed heat sinks subjected to natural convection and found that the Nusselt number for embossed fin increased with the impression angle and pitch. The effect of heat sink geometries on the performance of a thermoelectric generator was researched by Özbektas et al [21], who found that the electrical output increased with increasing air velocity and surface temperature. The application of heat sinks with a similar structure in a heat exchanger devices has not been thoroughly investigated, nor have the pressurized directional flow characteristics or the impact of the geometric parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Ozbektas et al [20] studied the cooling performance of a heat sink with flat fins on a TEG. The same authors also investigated whether a fin heat sink was used to obtain higher efficiency by cooling the TE more effectively [21]. Pujol et al [22] proposed a method to obtain the optimum plate-fin heat sink with forced convection.…”
Section: Introductionmentioning
confidence: 99%